eIF5 has GDI activity necessary for translational control by eIF2 phosphorylation - Jennings, Martin D. (2010)
In protein synthesis initiation, the eukaryotic translation initiation factor (eIF) 2 (a G protein) functions in its GTP-bound state to deliver initiator methionyl-tRNA (tRNA(i)(Met)) to the small ribosomal subunit and is necessary for protein synthesis in all cells1,2. Phosphorylation of eIF2 [eIF2(αP)] is critical for translational control in diverse settings including nutrient deprivation, viral infection and memory formation3,4,5. eIF5 functions in start site selection as a GTPase accelerating protein (GAP) for the eIF2•GTP•tRNA(i)(Met) ternary complex (TC) within the ribosome bound pre-initiation complex6,7,8. Here we define new regulatory functions of eIF5 in the recycling of eIF2 from its inactive eIF2•GDP state between successive rounds of translation initiation. Firstly we show that eIF5 stabilizes the binding of GDP to eIF2 and is therefore a bi-functional protein that acts as a GDP dissociation inhibitor (GDI). We find that this activity is independent of the GAP function and identify conserved residues within eIF5 that are necessary for this role. In addition we show that eIF5 is a critical component of the eIF2(αP) regulatory complex that inhibits the activity of the guanine-nucleotide exchange factor (GEF) eIF2B. Together our studies define a new step in the translation initiation pathway, one that is critical for normal translational controls.